THE CONSOLIDATION OF THE SKATING STEP FOR THE PHYSICAL EDUCATION AND SPORT STUDENTS THROUGH A "UPBALL-SKATING" INOVATIVE GAME - Pața Oana Cristina (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
The paper started from the premise that by introducing in the skating lessons to students of the Faculty of Physical Education and Sport, a ball game with own regulation and specific conditions of deployment, better results can be achieved on strengthening the skating step and thus sliding on the ice, under conditions of changing the direction of the slide and the position of the body during the slide, but also the development of driving qualities speed and coordination. The introduction of a game, with a ball in conditions of sliding on the ice, was a method by which the aim was to strengthen and achieve the skating step in everchanging and different conditions, created by both the opponent and the rules of the game. The game was introduced in the skating lessons after the basic training was done and all the students learned to skate. It initially unfolded as a game of motion, but in the process it required the development of rules to support students and to eliminate the danger of injury.